Human papillomavirus vaccination uptake in low-and middle-income countries: a meta-analysis - Dorji, Thinley (EClinicalMedicine, 2021)
BACKGROUND: The proportion of incident cases of HPV-attributable cancers is highest in the low- and middle-income countries (LMICs) but many are yet to initiate HPV vaccination programs. This meta-analysis was performed to assess the uptake of HPV vaccination in LMICs at the beginning of the global strategy to eliminate cervical cancer and describes the gaps and challenges. METHODS: A systematic search was conducted in PubMed, EMBASE, Scopus, Web of Science, and CENTRAL databases for observational studies that reported the uptake of HPV vaccination until October 2020. The meta-analysis was done using a random-effects model to assess the pooled estimate of HPV uptake. CRD42021218429 FINDINGS: During 2008–2020, an estimated 3.3 million females received at least one dose of HPV vaccine with 61.69% of the target population vaccinated. In countries with high uptake, the pooled estimate of uptake was higher in females than males (45.48% vs 8.45%) and showed significant decline in 2015–2020 compared to 2006–2014 (89.03% vs 41.48%). In countries with low uptake, the estimate of uptake was low in both males and females (5.31% vs 2.93%) and showed increase in uptake in 2015–2020 compared to 2006–2014 (0.76% vs 5.22%). In countries with high uptake, compared to routine programs, the estimate was higher when delivered through demonstration programs (89.94% vs 59.74%). INTERPRETATION: The major concern was a significant drop in the uptake in countries that started with high uptake, challenges in the maintenance of vaccine uptake, sustainability of funding and the lack of standard monitoring and reporting.